(3GdQhVJjf aj CNHGQ GdOhdJjf (B((3GdfhQjI hGdUdGMjI(B)s - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s ((3CMeO Hf GdYde Hf YHO Gddg s)
(3ChdgG (B:s
(3CeG HYO , aEfg HYO Cf UQbaJ Md YeQi ai GbJHGS GdahGFO GdTQYjI Ynqf di Cf CUQa Edi Yde GdJGQjN HYVg s
(3BNQgG (B:s
(3hGddg jWjd ddehdi dYeQ ceG CWGd dg ai GdbOQ hjSeY efg hdG jSeY ajg hjHbjg SfOkG ddOjf GdMfai , aEf HbGg jcajg BNQ GdLRA GdChd s
(3GfXQ Qbe(B" 1086" (3JGQjNs
(3YdjgG SeGYGJs
(3fSNI SGOSIs
(3fSNI efbhdI Yf fSNI fLe GdOjf Hf UUQj GdTGaYj s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs